Development of PUME as an educational game to optimize students' creative mathematical thinking ability in solid geometry topics - Apriliani, Sundari; Komala, Elsa; Sugiarni, Rani; Setiawan, Erwan; Sutandi, Andi (Polyhedron International Journal in Mathematics Education, 2024)
This study aims to develop a learning medium in the form of a game used for practice questions through PUME in the Solid Geometry topic to optimize creative thinking abilities. The method used in this study is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants for evaluating the feasibility of PUME included 4 media experts and 3 content experts consisting of lecturers and teachers, while the participants for assessing effectiveness were eighth-grade junior high school students from Cianjur district. The data collection techniques used in this study were a test of students' creative mathematical thinking abilities and expert judgment (validation by media experts, content experts, and student responses). The data analysis techniques used in this study involved qualitative data analysis (data reduction, data presentation, conclusion drawing) and quantitative data analysis in the form of percentage validation by media experts, content experts, and student responses using random sampling. The results of the study on the development of PUME as a learning medium for the Solid Geometry topic in the form of an educational game show that it can optimize students' creative mathematical thinking abilities. The feasibility level of PUME was rated as “very feasible,” and the effectiveness of PUME was classified as “effective” for implementation in mathematics learning for the Solid Geometry topic in junior high schools. As for students' creative mathematical thinking abilities, 45% of the students were nearly able to optimize their abilities.